2021
DOI: 10.33746/fhj.v8i03.295
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Efikasi Diri terhadap Kepatuhan Perawatan Kaki Diabetes Melitus pada Masa Pandemi

Abstract: Efikasi diri merupakan salah satu faktor pendorong dalam melakukan perilaku kepatuhan pengelolaan penyakit diabetes melitus dalam melakukan perawatan kaki untuk mencegah terjadinya komplikasi amputasi. Sementara itu, pada masa pandemi perhatian penderita diabetes melitus berfokus pada pecegahan covid-19. Penelitian ini bertujuan untuk mengetahui hubungan antara efikasi diri terhadap kepatuhan perawatan kaki penderita diabetes melitus. Metode penelitian ini adalah kuantitatif dengan desain penelitian cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Based on research conducted by Andini et al (2021), "the relationship of self-efficacy with behavior and accuracy of independent foot care actions in outpatients with diabetes mellitus" shows that there is a positive relationship between self-efficacy and behavior and the accuracy of independent foot care actions in outpatients with diabetes mellitus. The same study conducted by Susilawati et al (2021) with the title "The relationship of self-efficacy to adherence to diabetes mellitus foot care during a pandemic" also concluded that there is a significant relationship between self-efficacy and foot care adherence in people with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Based on research conducted by Andini et al (2021), "the relationship of self-efficacy with behavior and accuracy of independent foot care actions in outpatients with diabetes mellitus" shows that there is a positive relationship between self-efficacy and behavior and the accuracy of independent foot care actions in outpatients with diabetes mellitus. The same study conducted by Susilawati et al (2021) with the title "The relationship of self-efficacy to adherence to diabetes mellitus foot care during a pandemic" also concluded that there is a significant relationship between self-efficacy and foot care adherence in people with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 88%
“…According to Ratnawati (2016) in (Susilawati et al ( 2021) the higher level of self-efficacy will lead to good confidence in carrying out self-care in diabetes management, including foot care. This is supported by a study Susanti et al (2020) entitled "The relationship between self-efficacy and foot self-care in diabetes mellitus patients at the Internal Medicine Polyclinic of Sultan Syarif Mohamad Alkadrie Pontianak Hospital," which said that self-efficacy is very important in managing the health behaviors of diabetics.…”
Section: Relationship Of Self Efficacy With Foot Care Behavior In Dia...mentioning
confidence: 99%
“…Manajemen diri pada pasien diabetes dapat mencerminkan perilaku pasien secara sadar serta keinginan diri sendiri untuk mengendalikan penyakit DM (Susilawati et al, 2021). Manajemen perawatan diri penderita DM didasari pada 5 pilar, yaitu edukasi, diet, olahraga, farmakologi dan kontrol gula darah.…”
Section: Pendahuluanunclassified